THE CHARACTERISTICS OF BASE OF CONDUCTOR IN X GEOTHERMAL FIELD BASED ON THE MAGNETOTELLURIC AND WELL DATA: KARAKTERISTIK BASE OF CONDUCTOR DI LAPANGAN PANAS BUMI X PULAU FLORES BERDASARKAN DATA MAGNETOTELLURIK DAN SUMUR EKSPLORASI - Dizanissa Purnama Sari; Yunus Daud; Haris Siagian (Buletin Sumber Daya Geologi, 2023)
The X Geothermal Field in Flores, East Nusa Tenggara, has surface thermal manifestations such as hot springs, fumaroles, and alteration rocks, which indicate potential geothermal resources. This research aims to model and characterize the base of the conductor in X geothermal field as a supporting data for geothermal exploration studies. The modeling was performed using 3D magnetotelluric inversion analysis that was correlated with well data, i.e, drill cuttings, methylene blue, and Pressure and Temperature Test. According to the results, the subsurface condition of the study area consists of an argillic zone around 400-300 masl, a transition zone around 300 and 0 masl, and a propylitic zone below 0 masl. At an elevation of 400-300 masl, the base of conductor marks the boundary between the reservoir and the clay cap. The BOC distribution map reveals that the average BOC elevation is between 300 and 550 meters above sea level. The exploration potential is in the northern part with a prospect area of 3,4 km2 in research.